Improvement in IAPT outcomes over time: are they driven by changes in clinical practice?. (2020) - Saunders, Rob; Cape, John; Leibowitz, Judy; Aguirre, Elisa; Jena, Renuka; Cirkovic, Mirko; Wheatley, Jon; Main, Nicole; Pilling, Stephen; Buckman, Joshua E.J.
Abstract: Treatment outcomes across Improving Access to Psychological Therapies (IAPT) services in England have improved year-on-year, with the national average proportion of patients in recovery at the end of treatment now exceeding the 50% target. This is despite the number of referrals and numbers of treated patients also increasing year-on-year, suggesting that services have evolved local practices and treatment delivery to meet needs whilst improving performance. This study explores whether there have been changes in clinical practice with regard to: (1) the number of sessions and length of treatments; (2) the number of cancellations and non-attendance; and (3) the recording of problem descriptor information, and the association with treatment outcomes in IAPT. Routinely collected data from seven IAPT services involved in the North and Central East London (NCEL) IAPT Service Improvement and Research Network (SIRN) were brought together to form a dataset of nearly 88, 000 patients who completed a course of IAPT treatment. Results showed that there was a slight increase in the average number of sessions, and decreases in the length of time in treatment, as well as decreases in both the number of non-attended appointments and the use of inappropriate problem descriptors. These findings highlight a number of areas where potentially small changes to clinical practice may have had positive effects on patient outcomes. The value of using IAPT data to inform service improvement evaluations is discussed. Key learning aims: (1) How changes to treatment-delivery factors are associated with IAPT patient outcomes. (2) The link between clinical practice and potential service performance. (3) How analysing routinely collected data can be used to inform service improvement.